The Moderated Impact of Deviden Policy on Profitability to Firm Values; - susetyo, achmad budi; Febriyanti, Novi (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
The increasing public interest in investment, prompting a wider range of investment options, from the money market to the stock market. In the stock market there are quite a number of investment modes, both preferential and ordinary stocks and their derivatives, all of which can be measured from the fundamental side, both in terms of profitability, deviden, to the value of the Company. The study aims to investigate the impact of profitability and dividend policy on the value of the company, whose target company is an indexed issuer of the Jakarta Islamic Index (JII) in the period 2022-2023. Data collection method used using purposive sampling with data sources as secondary data. The analytical tool used in this study is Moderated Regression Analysis. The results of the research show that the deviden policy has a role as a moderating homologizer, which means these variables have the potential to moderate the power of influence between the profitability and value of the company. As for the direction of influence, the deviden policy has a positive impact, where the larger the dividend distributed, the higher the company's value achieved.